The effect of the sociodemographic determinants of self-monitoring of blood pressure - Dabi Wake, Addisu Dabi; Bekele, Daniel Mengistu; Bekele, Yohannes Ayalew; Tuji, Techane Sisay; Jaleta, Desalegn Tariku (Journal of Cardiovascular Medicine and Cardiology, 2021)
Introduction: Self-monitoring of Blood Pressure (BP) among hypertensive patients is a significant for the management and prevention of hypertension related complications such as atherosclerosis, Heart Failure (HF), Coronary Artery Disease (CAD), stroke, kidney disease, and peripheral arterial disease. Objective: The aim of the present study was to determine the effect of the sociodemographic determinants of Self-monitoring of BP in hypertensive subjects. Methods: A cross-sectional survey was done on four hundred hypertensive individuals on follow-up at selected hospitals in Arsi Zone, Ethiopia. The data collection period was from March ten to April eight, 2019. Result: In the present study, four hundred participants were included into the study. Age ≥60 years [AOR=2.01, 95% CI (1.82, 10.05), p=0.012], higher education [AOR=2.97, 95% CI (1.85, 14.33), p=0.002], governmental employed [AOR=1.56, 95% CI (1.08, 7.48), p=0.023], urban residents [AOR=1.61, 95% CI (1.17, 6.67), p=0.007], having a monthly income of > 3500 Ethiopian birr [AOR=2.46, 95% CI (1.87, 9.32), p=0.006] were factors significantly associated with self-monitoring of BP in the multivariable logistic regression analysis. Conclusion: In the present study; young adults, attended lower education, unemployed, rural residents, low monthly income patients were found to have poor self-monitoring of BP practice. Since, these patients are affected in particular, all the concerned bodies should actively participate to prevent or minimize this critical problem. During this, health education and training, on self-monitoring of BP may be required to take place.